Postoperative stereotactic radiosurgery compared with whole brain radiotherapy for resected metastatic brain disease (NCCTG N107C/CEC·3): a multicentre, randomised, controlled, phase 3 trial. Issue 8 (August 2017) - Brown, Paul D; Ballman, Karla V; Cerhan, Jane H; Anderson, S Keith; Carrero, Xiomara W; Whitton, Anthony C; Greenspoon, Jeffrey; Parney, Ian F; Laack, Nadia N I; Ashman, Jonathan B; Bahary, Jean-Paul; Hadjipanayis, Costas G; et al.
Summary: Background: Whole brain radiotherapy (WBRT) is the standard of care to improve intracranial control following resection of brain metastasis. However, stereotactic radiosurgery (SRS) to the surgical cavity is widely used in an attempt to reduce cognitive toxicity, despite the absence of high-level comparative data substantiating efficacy in the postoperative setting. We aimed to establish the effect of SRS on survival and cognitive outcomes compared with WBRT in patients with resected brain metastasis. Methods: In this randomised, controlled, phase 3 trial, adult patients (aged 18 years or older) from 48 institutions in the USA and Canada with one resected brain metastasis and a resection cavity less than 5·0 cm in maximal extent were randomly assigned (1:1) to either postoperative SRS (12–20 Gy single fraction with dose determined by surgical cavity volume) or WBRT (30 Gy in ten daily fractions or 37·5 Gy in 15 daily fractions of 2·5 Gy; fractionation schedule predetermined for all patients at treating centre). We randomised patients using a dynamic allocation strategy with stratification factors of age, duration of extracranial disease control, number of brain metastases, histology, maximal resection cavity diameter, and treatment centre. Patients and investigators were not masked to treatment allocation. The co-primary endpoints were cognitive-deterioration-free survival and overall survival, and analyses were done by intention to treat. We report the final analysis. This trial is registered with ClinicalTrials.gov, number NCT01372774 . Findings: Between Nov 10, 2011, and Nov 16, 2015, 194 patients were enrolled and randomly assigned to SRS (98 patients) or WBRT (96 patients). Median follow-up was 11·1 months (IQR 5·1–18·0). Cognitive-deterioration-free survival was longer in patients assigned to SRS (median 3·7 months [95% CI 3·45–5·06], 93 events) than in patients assigned to WBRT (median 3·0 months [2·86–3·25], 93 events; hazard ratio [HR] 0·47 [95% CI 0·35–0·63]; p<0·0001), and cognitive deterioration at 6 months was less frequent in patients who received SRS than those who received WBRT (28 [52%] of 54 evaluable patients assigned to SRS vs 41 [85%] of 48 evaluable patients assigned to WBRT; difference −33·6% [95% CI −45·3 to −21·8], p<0·00031). Median overall survival was 12·2 months (95% CI 9·7–16·0, 69 deaths) for SRS and 11·6 months (9·9–18·0, 67 deaths) for WBRT (HR 1·07 [95% CI 0·76–1·50]; p=0·70). The most common grade 3 or 4 adverse events reported with a relative frequency greater than 4% were hearing impairment (three [3%] of 93 patients in the SRS group vs eight [9%] of 92 patients in the WBRT group) and cognitive disturbance (three [3%] vs five [5%]). There were no treatment-related deaths. Interpretation: Decline in cognitive function was more frequent with WBRT than with SRS and there was no difference in overall survival between the treatment groups. After resection of a brain metastasis, SRS radiosurgery should be considered one of the standards of care as a less toxic alternative to WBRT for this patient population. Funding: National Cancer Institute.